The pressure $p$, and the density, $\rho$, of the atmosphere at a height $y$ above the earth's surface are related by $dp = -g \rho\; dy$. Assuming that $p$ and $\rho$ satify the adiabatic equation of state $p = p_0(\rho/\rho_0)^\gamma$, where $\gamma \neq 1$ is a constant and $p_0$ and $\rho_0$ denote the pressure and density at the earth's surface, respectively, show that

$$p = p_0\left[1 - \frac{\gamma - 1}{\gamma} \left(\frac{\rho_0 g y}{p_0}\right)\right]^{(\gamma - 1)/\gamma}$$


My work:

I separated variables and got $p = -g\rho y + c$. That's as far as I got.

  • $\begingroup$ Sorry to tell you this, but since $\rho$ is a function of $y$, even the first step you took is incorrect. $\endgroup$ – David K Aug 28 '15 at 1:23
  • 1
    $\begingroup$ If I remember correctly, the exponent of the correct equation for pressure is $(\gamma - 1)/\gamma$, not $(\gamma - 1/\gamma)$. Did you copy the formula incorrectly? That will make it harder to confirm when you get the right answer. $\endgroup$ – David K Aug 28 '15 at 1:26

to make typing easier, i will use $k, r$ for $\gamma$ and $\rho$ respectively.

we are given $$ dp = -gr dy, \, p = p_0 (r/r_0)^k.$$ we will solve for $r$ first, and then use the second relation to get hold of $p.$

taking logarithm and differentiating the $p$-$r$ relation gives us $$ k\frac{dr}r = \frac{dp}{p} = -\frac{gr\,dy}p = -\frac{gr_0^kr\, dy}{p_0r^k} $$ separating the variables $$kr^{k-2} \, dr = -\frac{gr_0^k}{p_0}\, dy $$ and on integration yields $$\frac k{k-1}\left(r/ r_0\right)^{k-1} = -gy+C$$ setting the initial condition $r =r_0$ at $y= y_0$ gives $$(r/r_0)^{k-1} = \frac{k-1}{k}\left( \frac k{k-1}-gy\right)=1-\frac{k-1}kgy $$

i hope you can complete the rest.


You are given two equations:

$$dp = -g \rho\; dy \tag1$$


$$p = p_0(\rho/\rho_0)^\gamma. \tag2$$

You cannot simply integrate both sides of $(1)$, treating $\rho$ as a constant, because in fact $\rho$ is less at high altitudes than at low altitudes; it is not constant. What you can do is use $(2)$ to eliminate $\rho$ from $(1)$, leaving you with an equation involving only $p$, $y$, and some constants. You can then do your separation of variables and integrate.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.